A naïve ontology for concepts of time and space for searching and learning - M. Miwa; N. Kando (Information Research: An International Electronic Journal)
Introduction. In this paper, we propose a new approach for developing a naïve ontology as the basis for optimal information access interfaces for multimedia digital documents intended for novice users. Method. We try to elicit the knowledge structure of domain novices and patterns of its modification in their searching and learning processes by eye-tracker and showing eye-movements in the post-search interviews. Analysis. Recorded interview data were fully transcribed and coded using Atlas.ti and analysed following a bottom-up strategy of the constant-comparative technique. Results. We developed a taxonomy of knowledge modification which includes (1) adding, (2) correcting, (3) limiting, (4) relating, (5) specifying and (6) transforming. Conclusion. The taxonomy may be expanded and elaborated as the project progress and findings are expected to be incorporated into the design of the naïve ontology. The study results provided theoretical implications on knowledge building, methodological implications on data collection using eye-tracker and showing eye-movements in the post-search interviews and useful information on the design of information access interface for novices users.